Design electronic ballast due to overvoltage protection/ Mohd Noh Sarip - Sarip, Mohd Noh (1998)
This project explores the simulation of an overvoltage protection circuit (less than 6kV) for the electronic ballast of a fluorescent lamp. The effective Metal Oxide Varistor (MOV) is suitable for use in maintaining the normal voltage supply 220V-240V before any damage can been done to the circuit components.